Neuroethics in Principle and Praxis Conceptual Foundations - Larrivee, Denis (IntechOpen, 2019)
With the conclusion of the Decade of the Brain and Decade of the Mind, neuroscience has advanced well beyond single neuron functions, and begun to investigate global properties that emerge from central nervous system operation. Core ethical issues for neural intervention, in consequence, now touch on concerns over how the individual as a whole may be affected. Central to these concerns is the fundamental value of the human being, which lends normative weight to questions, interventions, and practices influencing him or her. Yet, despite wide recognition of the crucial relevance of human value, the derivation of metaethical principles that underwrite this value is by no means uniformly agreed to. Why and how the human being is normatively privileged, accordingly, emerge as core questions that frame issues of ethical praxis. This book tackles this dissonance, and exposes the philosophical foundations that are rooting contemporary divisions in ethical approaches to intervention in the nervous system.